Development of a Decision Support System for Analysis and Solutions of Prolonged Standing in the Workplace - Ahmad Rasdan, Ismail; Isa, Halim; Hambali, Arep; Seri Rahayu, Kamat; Rohana, Abdullah; Abdul Rahman, Omar (Elsevier, 2014)
Prolonged :standing has been hypothesized as a vital contributor to discomfort and muscle fatigue in the workplace. The objective of this study was to develop a decision support system that could provide systematic analysis and solutions to minimize the discomfort and muscle fatigue associated with prolonged standing. The integration of object-oriented programming and a Model Oriented Simultaneous Engineering System were used to design the architecture of the decision support system.Results: Validation of the decision support system was carried out in two manufacturing companies. The validation process showed that the decision support system produced reliable results. Conclusion: The decision support system is a reliable advisory tool for providing analysis and solutions to problems related to the discomfort and muscle fatigue associated with prolonged standing. Further testing of the decision support system is suggested before it is used commercially.